Determinants of WhatsApp and Telegram usage for learning support in Nigerian universities: a quantitative study - Elom, Chinyere Ori; Ayerakwa, Hayford Mensah; Ibrahim-Olesin, Sikiru; Deffor, Eric Worlanyo; Uwaleke, Chidebe Chijioke; Onyeneke, Robert Ugochukwu (Frontiers in Education, 2025)
Evidence on the use of social media platforms such as WhatsApp and Telegram as learning support to enhance students’ performance is scarce in sub-Saharan Africa, where there is limited application of such platforms for learning. Much rarer are studies analyzing the determinants of using WhatsApp and Telegram as learning support to enhance students’ performance in the region. We used cross-sectional data from 206 students from public universities in Nigeria and applied econometric frameworks (such as Pearson’s correlation and multivariate regression analysis) to analyze the determinants of social media platforms such as WhatsApp and Telegram as learning support among university students in Nigeria. We identified six constructs of using WhatsApp and Telegram as learning support in Nigerian public universities, which include performance expectancy, effort expectancy, social influence, institutional and political influence, guidance and counseling achievements, and facilitating conditions. These constructs were acceptable/accepted by the students. The determinants of the use of WhatsApp and Telegram to enhance learning among students include age, gender, wealth status of parents/guardians, student’s faculty/program, location of school, and level of student in school. The constraints to students’ usage of WhatsApp and Telegram for learning support include high cost of Internet, poor connectivity and epileptic/poor power supply to charge phones, mistrust, lack of structure and coherence, and irresponsible use of social media. The results have significant implications for educational institutions, policymakers, and stakeholders seeking to promote the effective use of mobile learning technologies.